Pengelolaan Layanan Perpustakaan Berbasis Sistem Manual di Dinas Perpustakaan dan Kearsipan Kota Payakumbuh - Robby Dzakwan; Marlini Marlini (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The Library and Archives Office of Payakumbuh City is a government institution providing information services to the community. Most library services are still managed manually, including recording book loans and returns, as well as visitor administration. This study aims to describe the management of manual-based library services in the institution. The research employed a qualitative descriptive method with data collection through direct observation and documentation. Data were obtained from the author’s internship experience, including observation of service workflows, manual record-keeping, and documentation of loan books and visitor logs. The results show that library services still operate using a manual system with high dependence on staff accuracy. Identified challenges include longer service time, potential recording errors, and difficulties in retrieving historical data. Nevertheless, the manual system can support service continuity if proper administrative discipline is maintained.This study provides an actual overview of regional library service practices and serves as an initial reference for developing more efficient service systems in the future.